Awareness of Child Maltreatment among Professionals in Shanghai. Issue 3 (18th September 2015) - Shang, Xiaoyuan; Katz, Ilan
<x xml:space="preserve">Abstract</x> This study reports on a series of qualitative interviews with professionals in Shanghai, China who work with children. The interviews explored the awareness of child protection issues amongst a range of people who work with children, how they differentiate corporal punishment from maltreatment and what they would do in response to cases of child abuse. Shanghai has one of the most well developed child welfare systems in China, and compared to similar professionals in other cities, those in Shanghai had higher awareness and more training, but were nevertheless reluctant to intervene and did not feel well prepared to deal with cases of child abuse should they be encountered. However there are some indications that practice is improving, and examples of recent developments are provided.